Engine Testing In Dyno Close Loop Simulation Environment - et. al., Miss. Shraddha Vinod Khadilkar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Considering the advancement in technology and automation, there is wide scope for software simulation tools for testing. Hardware in Loop (HIL) is the most important and popular tool from Small control applications to complicated energy systems and machines. This paper focused on the HIL simulation platform to test Engine features. The main objective of using HIL is to simulate test scenarios to validate and verify customer-used cases. Engine development mainly includes designing, prototyping, testing, and manufacturing. Testing is an important element in the development process. Engine testing allows you to verify the product is designed correctly and validate that the right product has been designed for the right application. Testing on the assembled engine for performance validation and verification is always the ideal case, but it also incurs significant test overheads and challenges. Hardware in Loop (HIL) testing is a technique where a simulator replaces the real product and provides interface signals to the controller under test. This HIL assesses in terms of thousands of possible scenarios to validate your controller without the cost and time associated with actual physical tests. This paper presents the application of hardware in loop simulation testing for verification and validation field used cases in dyno close-loop environment.